Discursive Entrapment and the Limits of Potentiality in Plyer v. Doe - Romero, Alé (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2024)
This essay traces the enduring legacy of the figure of the child leading up to and at the centre of the 1982 Plyler v. Doe decision. I attempt to demonstrate the limits of the discursive deployment of the child figure for racialized subjects. This essay intervenes in education, childhood studies, and immigration literature by reading the child to understand the enduring legacy of Plyler for those who are not the central focus of the court case. I demonstrate how the necessity of matriculating into U.S. schools is implicated in politics of disposability for racialized gendered populations represented in reading the contradictions in immigration reform.